Geriatric Nutritional Risk Index in Predicting the Mortality of Fournier’s Gangrene: Analysis of 14-Year Statistics of Referral Center - Alinejad Khorram, Amir; Hojjati, Seyyed Ali; Sodeifian, Fatemeh; Kolahchi, Roya; Farjami, Mohammad; Rahnama, Hossein; Allameh, Farzad (Archives of Academic Emergency Medicine, 2024)
Introduction: Fournier’s gangrene (FG) is a type of necrotizing fasciitis affecting the external genitalia or perineum. The Geriatric Nutritional Risk Index (GNRI) has been reported as a prognostic factor to evaluate the outcomes of various diseases. This study aimed to investigate the utility of GNRI in predicting the mortality of FG patients. Methods: This retrospective cross-sectional study evaluated the patients admitted to a referral hospital, during 14 years, with diagnosis of FG. The role of GNRI in predicting the mortality of these patients was studied. To further investigate the relationship of the GNRI score with patients’ prognosis, we controlled for the scores of Fournier’s Gangrene Severity Index (FGSI) and Charlson Comorbidity Index (CCI). Result: 78 patients with the mean age of 60.79 ± 13.76 (range: 24 -85) years were included in the study (89.74% male). The mortality rate in this series was 23 (29.5%) cases. The survived cases had significantly higher GNRI score (p < 0.001), higher Albumin level (p < 0.001), higher weight (p = 0.04), and lower mortality risk based on FGSI score (p < 0.001). In patients with low mortality risk according to FGSI score (p = 0.036) and mild comorbidities based on CCI score (p = 0.030), the association between GNRI and final prognosis was significant. In contrast, in patients with high mortality risk according to FGSI score (p =0.074) and moderate (p = 0.118) and severe (p = 0.215) comorbidities by CCI score this association was not significant. The independent predictors of mortality in FG patients were GNRI score (OR: 1.242, 95%CI: 1.08, 1.41; p =0.001) and FGSI score (OR: 54.614, 95%CI: 6.89, 432.31; p < 0.001). The area under the receiver operating characteristic (ROC) curve of GNRI score in predicting the mortality of FG patients was 0.84 (95%CI: 0.75 - 0.93). The sensitivity, specificity, positive predictive value, negative predictive value, positive likelihood ratio, and negative likelihood ratio of GNRI score at the optimal cut-off point (78.5) were, 80%, 77.9%, 60.6%, 90.4%, 3.69, and 0.255 respectively. Conclusions: Our findings indicate that among patients with mild FG, as assessed by FGSI score, and those with low comorbidities based on CCI score, the GNRI score in survivors was significantly higher than that in non-survived. Additionally, multivariate regression analysis demonstrated that the GNRI score serves as an independent predictor of patient outcomes.